Definition of Terms Used in the National Organic Program - James J. Ferguson (EDIS)
The National Organic Program (NOP) under the direction of the Agricultural Marketing Service, United States Department of Agriculture was established to "facilitate domestic and international marketing of fresh and processed food that is organically produced and assure consumers that such products meet consistent, uniform standards." The final rule of the National Organic Program covers production, packing and processing, marketing, retailing, and other aspects of organic operations. Given the complexity of regulatory aspects of the National Organic Program, a set of definitions (107 terms) has been developed to clarify the meaning of specific words and phrases. This set of definitions is included here to make this information more easily accessible. This document is HS963, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2004.